1996
DOI: 10.1097/00005392-199603000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 Versus Mixture of Prostaglandin E1, Papaverine and Phentolamine in Nonresponders to High Papaverine Plus Phentolamine Doses

Abstract: The 3-drug mixture may be regarded as more effective than prostaglandin E1 alone in inducing an erectile response with a decreased incidence of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
2
12
1
Order By: Relevance
“…The latter finding is not consistent with the results of a prospective study performed by Bechara et al, 18 who showed that the three-drug mixture is more effective than high-dose PGE1 alone in achieving erections suitable for penetration. However, our satisfaction and compliance rates are similar to those of Mulhall et al 3 and Purvis et al 6 Using an institutional questionnaire, Mulhall et al found a good response in 75% of their patient group using PGE1, which included patients with ED of all etiologies.…”
Section: Discussioncontrasting
confidence: 79%
“…The latter finding is not consistent with the results of a prospective study performed by Bechara et al, 18 who showed that the three-drug mixture is more effective than high-dose PGE1 alone in achieving erections suitable for penetration. However, our satisfaction and compliance rates are similar to those of Mulhall et al 3 and Purvis et al 6 Using an institutional questionnaire, Mulhall et al found a good response in 75% of their patient group using PGE1, which included patients with ED of all etiologies.…”
Section: Discussioncontrasting
confidence: 79%
“…6 In nonresponders to doses as high as 40 mg PGE 1 , Tx combination produced a response in 31%. 16 The cost of the medication is another important issue where Tx has an advantage ( Table 2). In men on ICI therapy, the total dropout rate was 31% and 28.3% dropped out because the therapy was too expensive.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published reports in this area concern the evaluation of specific diagnostic and therapeutic strategies. [1][2][3][4][5][6] Indeed, the field has advanced significantly in recent years with the advent of intracavernosal injection [7][8][9][10] and intraurethral therapy. 11 As health care increasingly moves to the primary care setting, generalists must be more attuned to the pathophysiology, treatments, and psychosocial impacts of erectile dysfunction in their patients.…”
mentioning
confidence: 99%